Chlorate occurrence in drinking water - Briones Carles, Pablo (Cranfield University, 2023)
The use of chlorine for disinfection of potable water has been the major public health advancement in the last century. Sodium hypochlorite is currently used worldwide for potable water disinfection. Arising from sodium hypochlorite solutions, chlorate forms as the sodium hypochlorite ages. Chlorate has been recently regulated in the EU directive and is catalogued as a compound of concern for the Drinking Water Inspectorate. The WHO recommended in 2015 a guideline level of 0.7mg/L, and chlorate is currently set at level of 0.25 mg/L in potable water supplies. As chlorate was previously a guidance, and not extensively monitored, this presents a regulatory challenge for most water companies to adopt. From a large historical data set, from 2014 to 2020, it was extrapolated that chlorate monthly running average values were expectedly higher during the warmer season, likely explained by the increased chlorine demand during warmer months, but far from the current regulation limit for well-resourced sites. A questionnaire was completed in cooperation with operators and process scientist on site. The interviews were completed across various WTW in Scotland. The aim was to demonstrate the varying disinfection practices and extract conclusions on the hypothetical chlorate levels arising during the dosing and storage of sodium hypochlorite. The selection of sites provided a good overview on the particularities of the disinfection stage, from small WTW, where the sodium hypochlorite gets diluted on site, to large WTW with bulk storage of 15% sodium hypochlorite. Sites with a varied risk of chlorate occurrence were also included such as on-site electro-chlorination and chlorine gas disinfection. It was concluded that there are correct measures in place during the operation and maintenance of the disinfection stage, but chlorate levels during storage are not centrally reported. The questionnaire has shown some sites where the solutions of sodium hypochlorite were potentially exposed to warm temperatures and extended periods of storage. It is likely that high room temperature is the underpinning cause leading to sudden chlorate increase in combination with high chlorine demands during the warmer months. This emphasised the need for longitudinal studies on the degradation of hypochlorite solutions during storage. It has been identified that a robust supply chain providing fresh hypochlorite deliveries could be a major implementation aiming to tackle high chlorate levels, particularly for remote and isolated potable water treatment works. The need for an accurate determination of chlorine demand on site remains of crucial relevance aiming to adjust disinfectant capability across varying treatment processes. The importance of regular procurement of hypochlorite solutions and the need for contingency was emphasised by the operators in order to avoid high seasonal chlorate levels. As a part of the experimental plan, the aim was to analyse the long-term stability of sodium hypochlorite during storage with a focus on the impact of disinfectant concentration on chlorate formation. The decay rates for sodium hypochlorite solutions and chlorate formation have been determined at varying initial concentrations using incubation experiments in the laboratory. It was determined the application of consecutive refilling during sodium hypochlorite storage with remaining old solutions of hypochlorite. Via bench scale kinetic experiments, it was determined whether the use of a 10% free chlorine concentration of sodium hypochlorite is less prone to promote further chlorate formation compared to the currently used 15% hypochlorite solutions. It has been found the relative chlorate to free chlorine content remains high even after the adoption of lower concentration hypochlorite solutions. This has implications for sites currently using dilution of hypochlorite and high chlorine demands. Lower initial concentrations of sodium hypochlorite also presented more stability and remaining disinfectant capacity during the bench scale studies. It is concluded that extensive monitoring and control will be required in order to achieve tighter chlorate standards. The relative chlorate to free chlorine ratio (mg Chlorate/ mg of free chlorine) has been highlighted as a concern resulting from high values in diluted solutions of hypochlorite and on-site electro chlorination systems. Further mitigation strategies have been summarised discussing the risk factors for future chlorate occurrences, implementations aiming to tackle chlorate occurrence pre-emptively, and limit exceedances of the EU directive, now adopted in Scotland. Overall, the thesis provided a better understanding on the drivers prompting chlorate levels derived from sodium hypochlorite disinfection, a list of comprehensive evidence-based interventions at water treatment facilities and highlighted best management practices.
Jarvis, Peter - Associate Supervisor
Keywords: Drinking water disinfection; Inorganic DBPs; Sodium hypochlorite; best management practices; chlorine demand; dosing; storage